PENGARUH EROSI LAHAN TERHADAP ANGKUTAN SEDIMEN MELAYANG KECAMATAN LHOONG KABUPATEN ACEH BESAR - Maimun Rizalihadi; Khairul Iqbal; Juan Indra (JURNAL TEKNIK SIPIL, 2014)
The existence of Montara river is very crucial because it is the main source of irigation in Lhoong Subdistrict.  One of concerns that worhtly can be discussed in Montara river is the level of soil erotion. Erotion and sedimentaion study are done on July through August for a month or 10 days of rain (thoose that reached the first will be selected) he calculation of erotion used the USLE equation, while study about sediment in Krueng Montara Basin is narrowed only for suspended load. The results of this study are the amount of land erotion and the suspended load discharge in some rainfalls, the correlation between both of them is determined into some  regression models namely linear regression, power regression and exponential regression. The result shows that the power regression model is  the best model of all which has a formula as Qs = 6,7953 A1,8791 with R² = 0,8786 or 87 % and close to 1, it means this model can be used to predict the suspended load discharge by knowing the amount of land erossion and also the reverse. Besides using regression model, the relationship between land erossion (A) and  suspended load (Qs) s determined by calculating the suspended load ratio. Based on calculation, the average ratio of suspend load (Qs) in Krueng Montara basin is 0,00233.